Human cell‐derived microparticles promote thrombus formation in vivo in a tissue factor‐dependent manner - Biró, É.; Sturk‐Maquelin, K. N.; Vogel, G. M. T.; Meuleman, D. G.; Smit, M. J.; Hack, C. E.; Sturk, A.; Nieuwland, R. (Journal of thrombosis and haemostasis, 2003)
Background: Circulating microparticles of various cell types are present in healthy individuals and, in varying numbers and antigenic composition, in various disease states. To what extent these microparticles contribute to coagulation in vivo is unknown. Objectives: To examine the in vivo thrombogenicity of human microparticles. Methods: Microparticles were isolated from pericardial blood of cardiac surgery patients and venous blood of healthy individuals. Their numbers, cellular source, and tissue factor (TF) exposure were determined using flow cytometry. Their in vitro procoagulant properties were studied in a fibrin generation test, and their in vivo thrombogenicity in a rat model. Results: The total number of microparticles did not differ between pericardial samples and samples from healthy individuals (P = 0.786). In both groups, microparticles from platelets, erythrocytes, and granulocytes exposed TF. Microparticle‐exposed TF antigen levels were higher in pericardial compared with healthy individual samples (P = 0.036). Pericardial microparticles were strongly procoagulant in vitro and highly thrombogenic in a venous stasis thrombosis model in rats, whereas microparticles from healthy individuals were not [thrombus weights 24.8 (12.2–41.3) mg vs. 0 (0–24.3) mg median and range; P < 0.001]. Preincubation of pericardial microparticles with an inhibitory antibody against human TF abolished their thrombogenicity [0 (0–4.4) mg; P < 0.01], while a control antibody had no effect [19.6 (12.6–53.7) mg; P > 0.05]. The thrombogenicity of the microparticles correlated strongly with their TF exposure (r = 0.9524, P = 0.001). Conclusions: Human cell‐derived microparticles promote thrombus formation in vivo in a TF‐dependent manner. They might be the direct cause of an increased thromboembolic tendency in various patient groups.